Krytyka powieściopisarstwa Eugeniusza Sue w ujęciu Wincentego i Zygmunta Krasińskich = A criticism of the Eugene Sue`s writing from Wincenty and Zygmunt Krasiński`s perspective - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject matter of the research is Zygmunt Krasinski and his father`s opinions concerning thenovels of the famous French writer - "Eugene Sue". In 1833 Krasinski expressed his own opinion ona so-called "roman maritine", whereas, in 1845, his father, also in a very emotional way, presentedhis views on "The Wandering Jew". The author of the article observes the analogy between these twojudgments and the judgments of other experts in the field of the XIX century literature.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); Krasiński, Zygmunt (1812-1859); Krasiński, Wincenty (1782-1858); literatura francuska - krytyka